Journal of Biomedical Science - Chang, Wen-Chang
Journal of Biomedical Science is an open access, peer-reviewed journal that encompasses all fundamental and molecular aspects of basic medical sciences, with an emphasis on the molecular studies of biomedical problems and molecular mechanisms. The journal is supported by the Ministry of Science and Technology (MOST), Taiwan, who covers the cost of publication on behalf of the authors on acceptance of their article. Topics of interest include, but are not limited to: anatomic pathology biochemistry genetics immunology microbiology and virology molecular, cellular and cancer biology neurosciences pharmacology physiology Journal of Biomedical Science aims to provide an international forum for encouraging interdisciplinary discussions and contributing to the advancement of medicine, benefiting readers and authors by accelerating the dissemination of research information and providing maximum access to scholarly communication.